2018
DOI: 10.4314/gjedr.v17i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of 5Es’ constructivist approach for enhancing the teaching of difficult concepts in biology

Abstract: Studies show that students perform poorly at the secondary school level in biology. The concepts considered as difficult contribute more to the poor performance. The fact remains that the topics related to these concepts are found to be difficult by the teachers teaching them. The undesirable trend has been attributed among other reasons to ineffective pedagogy among teachers of biology. This problem led to an upsurge of research into innovative approaches that can alleviate the situation. One such emerging ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…In Indian, inquiry-based science instruction had a positive effect on students' science achievement (Ong et al, 2018). One of the strategies that can help teachers develop inquiry-based lessons is using 5E's educational learning circle approach, which consists of five phases: Engage, Explore, Explain, Elaborate, and Evaluate (Ihejiamaizu, et al, 2018) as Figure 1 illustrates.…”
Section: Inquiry-based Educational Modelmentioning
confidence: 99%
“…In Indian, inquiry-based science instruction had a positive effect on students' science achievement (Ong et al, 2018). One of the strategies that can help teachers develop inquiry-based lessons is using 5E's educational learning circle approach, which consists of five phases: Engage, Explore, Explain, Elaborate, and Evaluate (Ihejiamaizu, et al, 2018) as Figure 1 illustrates.…”
Section: Inquiry-based Educational Modelmentioning
confidence: 99%
“…Teachers create a learning environment appropriate to the learners' understanding and avoid mass production (Andala & Ng'umbi, 2016). It is believed that laying on a solid foundation in Physics education involves employing appropriate teaching and learning techniques (Ihejiamaizu et al, 2018) The 5Es' model is derived from the concept that learners learn the most, retain knowledge, and have an opportunity to connect prior knowledge to new information with the acquisition of higher concept understanding (Mustafa, 2016). This 5Es learning and teaching model includes higher-order thinking skills (Muhammad et al, 2021).…”
Section: The 5es Instruction Modelmentioning
confidence: 99%
“…Other studies within the same country showed that the lessons studied through the 5Es model enhanced learners' positive attitudes by providing better understanding, increased the motivation related to the lesson, and created a positive effect on understanding abstract concepts (Guzel, 2017). In a study by Ihejiamaizu et al (2018), it was found that teaching through 5Es instruction helped learners to improve their active participation in Physics. Similar studies conducted in Italy indicated that the 5Es instructional model helped the learners better understand the scientific concepts and getting interested in science and reasoning.…”
Section: The 5es Instruction Modelmentioning
confidence: 99%
See 2 more Smart Citations